La realidad política latinoamericana a la luz de la Carta Democrática Interamericana - Arrighi, Jean Michel (2021)
• Doctor Jean Michel Arrighi / • Embajador Hugo de Zela / • Profesor Emilio Nouel / • Profesora Raquel Gamus / • Embajador Eduardo Ponce